A hybrid indirect evaporative cooling-mechanical vapor compression process for energy-efficient air conditioning. (15th November 2021) - Chen, Qian; Kum Ja, M.; Burhan, Muhammad; Akhtar, Faheem Hassan; Shahzad, Muhammad Wakil; Ybyraiymkul, Doskhan; Ng, Kim Choon
Highlights: A hybrid indirect evaporative cooling-mechanical vapor compression process is evaluated. The indirect evaporative cooler can recover energy from room exhaust air to cool and dehumidify outdoor air. The indirect evaporative cooler handles 34–77% of the total cooling load. The hybrid system increases energy efficiency by 19–135%. Abstract: The indirect evaporative cooler (IEC) is deemed an effective and sustainable alternative to existing mechanical vapor compression (MVC) chillers in cooling applications. However, IEC is a passive cooler that has no effective control over the supply air temperature and humidity. Also, the performance of IEC degrades severely when the humidity of the air is high. To overcome these limitations, we investigate a hybrid process that connects IEC and MVC in tandem. The outdoor air is firstly pre-cooled in the IEC by recovering energy from the room exhaust air, and then it is further processed to the desired condition using MVC. Such a hybrid IEC-MVC process benefits from IEC's high energy efficiency and MVC's capability of humidity and temperature control. A pilot IEC unit with the cross-flow configuration is firstly constructed and tested under assorted outdoor air conditions. Employing the room exhaust air as the working air in the wet channels, the IEC simultaneously cools and dehumidifies the outdoor air. Under the operating conditions considered, the outdoor air temperature can be reduced by 6–15 °C, and the humidity ratio drops by 0.5–4 g/kg. The coefficient of performance (COP) for IEC is 6–16, leading to an overall COP of 4.96–6.05 for the hybrid IEC-MVC process. Compared with a standalone MVC, the electricity consumption can be reduced by 19–135%.